2011
DOI: 10.1016/j.engstruct.2011.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Testing and long-term monitoring of a curved concrete box girder bridge

Abstract: Abstract:Capital investment in national infrastructure is significant. The need to maintain and protect critical infrastructure links has led in recent years to significant developments in the area of structural health monitoring. The objective is to track a structure's long-term performance, typically using sensors, and to successively compare most recently measured responses with prior response history. During construction of the West Street On-Ramp, a curved concrete box girder bridge, located in the city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 23 publications
(24 reference statements)
0
33
0
Order By: Relevance
“…While some studies from literature showed that the stiffness of concrete bridge was reduced over time [7] [8] [11], others authors detected an increase [3] [4] or attacked the issue numerically [12]. Our observations of the above-mentioned sample bridge and the measurement of its first 3 eigenfrequencies show in general a decrease over the years.…”
Section: Introductionmentioning
confidence: 48%
“…While some studies from literature showed that the stiffness of concrete bridge was reduced over time [7] [8] [11], others authors detected an increase [3] [4] or attacked the issue numerically [12]. Our observations of the above-mentioned sample bridge and the measurement of its first 3 eigenfrequencies show in general a decrease over the years.…”
Section: Introductionmentioning
confidence: 48%
“…While abrupt changes in the dynamic properties of bridges are usually caused by a destructive event such as an earthquake, previous studies on long-term monitoring showed the natural frequencies of bridge structures follow a gradual and approximately linear decrease over the years (Soyoz and Feng 2009;Gomez, et al 2011). Such effects cannot be disregarded in an accurate structural health condition assessment.…”
Section: Modal Identificationmentioning
confidence: 92%
“…Currently, these methods are frequently used (e.g. Altunisik, Bayraktar, & Sevim, 2011;Brincker, Zhang, & Andersen, 2001;Gomez, Fanning, Feng, & Lee, 2011;Hadson, 1977;Jacobsen, Andersen, & Brincker, 2008;Maalek, Akbari, & Ziaei-Rad, 2010;Peeters & Ventura, 2003;Rodrigues, Brincker, & Andersen, 2004;Ubertini, Gentile, & Materazzi, 2013;Wenzel, 2009). Thus, in this study, through performing several operational modal tests and subsequent use of the well-known enhance frequency domain decomposition (EFDD) method, the dynamic characteristics of an urban bridge before, during and after widening have been identified.…”
Section: Introductionmentioning
confidence: 94%